A Voice in the Room: The Function of State Legislative Bans on Sexual Orientation Change Efforts for Minors. Issue 1 (March 2014) - Cella, Arcangelo S.
Abstract : Throughout the history of the mental health profession, many psychotherapists have asserted that homosexuality is a mental condition or defect that may be corrected through treatment. Homosexuality was not officially declassified as a mental illness until 1973, and it was not until recently that mainstream mental health organizations renounced the claim that therapy can alter sexual orientation. Sexual orientation change efforts (SOCE) involve various types of psychotherapy, from the familiar and seemingly benign talk therapy to forms of behavioral therapy that include "masturbatory reconditioning, rest, visits to prostitutes[, ] excessive bicycle riding, " and even physical abuse. SOCE are now widely regarded by mainstream mental health practitioners as unscientific, ineffective, and mentally and emotionally harmful. Nevertheless, due to persistent societal disapproval of homosexuality, some mental health providers continue to engage in SOCE, often causing their patients to experience shame and anxiety well into adulthood.